(untitled) (Altre Modernità, 2018)
The article proposes a comparative and text-oriented analysis of Vie de Henry Brulard and Le Rouge et le Noir and it wants to illustrate how elements of the Novel are evoked and recalled in the autobiographical writing by textual occurrences, following three themes: the presence of the father, the language, the erotic aspect. This analysis put under scrutiny how these interconnections between Fiction and Autobiography work, by showing how some autobiographical echoes that were firstly transposed in the Novel are re-elaborated and proposed again in the Autobiography after the contamination with Fiction. Thus, throughout the process of re-elaboration of mnemonic materials, memories could lose their bond with the historic event, which instead bring to the fore revealing signs of Stendhal’s personal truth.